REGIONAL FOCUS AND TAUTOMERICITY IN THE SERIES OF AROYLHYDRASONES OF β-DICARBONYL COMPOUNDS (Journal of Pharmaceutical Negative Results, 2022)
Nitrogen derivatives of β-ketoaldehydes are capable of various tautomeric transformations [1–5]. The condensation products of aroylacetic aldehydes with aromatic acid hydrazides exist in linear, hydrazone, and enhydrazine forms. The appearance of an alternative cyclic 5-hydroxy-2-pyrazoline form is facilitated by the introduction of a strong electron-withdrawing substituent into the aromatic ring of 1,3-ketoaldehyde. In series of compounds, an increase in the volume of the substituent in the acyl moiety shifts the tautomeric equilibrium towards the enhydrazine form. The resulting organic substances were studied by elemental analysis, IR and 1H NMR spectroscopy. The molecular structure of compound II was determined by X-ray diffraction analysis (CCDC no. 1826717).